SOLUBILITIES OF CARBON DIOXIDE AND WATER IN RHYOLITIC MELT AT 850°C AND 750 BARS - Blank J.G.; Stolper E.M.; Carroll M.R. (My University, 1993)
Concentrations of carbon dioxide and water dissolved in glasses quenched from rhyolitic melts equilibrated with H_2O-CO_2 fluids at 850°C and 750 bar were measured using infrared spectroscopy; concentrations of H_2O and CO_2 in the quenched fluids were measured manometrically. The mole fraction of CO_2 in the quenched fluid ranged from 0.06 to 0.91. Concentrations of CO_2 in the coexisting rhyolitic melt increased from 23(±6) ppm for the sample equilibrated with the most CO_2-poor fluid to 515(±16) ppm for that equilibrated with the most CO_2-rich fluid. The water content of the melt varied from 0.51(±0.06) to 3.34(±0.08) wt%. Our results show that concentrations of molecular CO_2 and H_2O in the glasses obey Henry's Law; i.e., the mole fractions of molecular CO_2 and molecular H_2O in the quenched melts are proportional to their fugacities in the coexisting vapor. CO_2 contents of vapor-saturated melts are not enhanced by addition of water to CO_2-rich vapor, contrary to previous reports for silicate melts at higher pressures. The Henrian behavior of CO_2 and H_2O at low pressure considerably simplifies modeling of the degassing of silicic magmas.